IMPLEMENTASI MEDIA VIDEO PADA PEMBELAJARAN PAI DI SMK DARUT TAQWA SENGONAGUNG PURWOSARI - Shoimatul Hikmah; Wiwin Fachrudin Yusuf; M. Anang Sholikhudin; Muhammada Muhammada (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2023)
The study of Video Media Implementation in Islamic Education Learning at SMK DarutTaqwa Sengonagung Purwosari was motivated by the existence of several problems encountered in the field, namely the conventional learning system, which only uses the lecture method, making students feel bored when receiving lessons and the classroom atmosphere becomes inactive, especially in the subject of Islamic cultural history (PAI). The formulation of the problems in this study are: 1) How is the implementation of video media in PAI learning at SMK Darut Taqwa Sengonagung Purwosari? 2) What are the advantages and disadvantages of video media implementation at SMK Darut Taqwa Sengonagung Purwosari? The approach in this research uses qualitative methods, data sources obtained include: observation, interviews, and documentation. This research was conducted in class XII TKJ 2 of SMK Darut Taqwa Sengonagung Purwosari. The results of this study are 1) the implementation of video media in PAI learning shows that learning using methods and learning media is quite flexible. 2) The advantages of implementing video media in learning some students stated that the implementation of video media can make them understand when receiving learning material, while the weakness is the implementation of video media teachers need time and careful preparation, so it takes a lot of time, So it can be concluded that the application of video media in the learning process has no difficulties for both teachers and students